Estudio de la coordinación y su influencia en la enseñanza de la técnica bandal chagui en niños de nueve años de edad que practican el taekwondo. Propuesta de una alternativa metodológica - Rojas Tapuy, Jairo Ricardo (2016)
The present investigation treated the practice of Taekwondo a sport of martial combat, the subject of research STUDY OF THE COORDINATION AND ITS INFLUENCE IN THE TEACHING OF BANDAL CHAGUI TECHNIQUE IN CHILDREN OF NINE YEARS OF AGE PRACTICING THE TAEKWONDO. PROPOSAL OF A METHODOLOGICAL ALTERNATIVE. Central problem How to propose a methodological guide based on the coordination exercises for the teaching of the chagui band technique in nine year old children who practice Taekwondo in the gymnasium of the Provincial Sports Federation of Napo in the Canton of Tena? General objective: To design a methodological alternative for the development of the basic bandagi chagui technique in nine-year-old boys and girls who begin the practice of Taekwondo in the gymnasium of the Provincial Sports Federation of Napo, Canton of Tena. Specific objective: To evaluate the means, methods and procedures used by sports coaches for the teaching of the chagui band technique in nine-year-old children who begin the practice of Taekwondo in the gymnasium of the Provincial Sports Federation of Napo, Canton of Tena. The methods facilitated the guide and orientation of the entire research process, thus guaranteeing the final result that is proposed, among them are highlighted. Methods The theoretical methods were used for analysis and synthesis, deduction-induction, hypothetical deductive, While the empirical ones are observation, measurement, description and techniques of content analysis. The population and sample was established by 2 trainers and 29 children belonging to that institution. The techniques and instruments used were; Surveys, observation and test sheets. We conclude the diagnosis made to the coaches allowed us to know that they do not use the methods and procedures in the teaching of the technique bandal chagui.